Students' implicit epistemologies when working at the intersection of engineering and the arts - Joshua Cruz; Noa Bruhis; Nadia Kellam; Suren Jayasuriya (SpringerOpen, 2021)
Abstract Background This paper explores the epistemologies and discourse of undergraduate students at the transdisciplinary intersection of engineering and the arts. Our research questions focus on the kinds of knowledge that students value, use, and identify within an interdisciplinary digital media program, as well as how they talk about using these epistemologies while navigating this transdisciplinary intersection. Six interviews were conducted with students pursuing a semester-long senior capstone project in the digital culture undergraduate degree program in the School of Arts, Media and Engineering at Arizona State University that emphasizes the intersection between arts, media, and engineering. Results Using deductive coding followed by discourse analysis, a variety of student epistemologies including positivism, constructionism, and pragmatism were observed. "Border epistemologies" are introduced as a way to think and/or construct knowledge with differing value across disciplines. Further, discourse analysis highlighted students' identifications with being either an artist or an engineer and revealed linguistic choice in how students use knowledge and problem-solve in these situations. Conclusions Students in a digital media program use fluid, changing epistemological viewpoints when working on their projects, partly driven by orientations with arts and/or engineering. The findings from this study can lead to implications for the design and teaching of transdisciplinary capstones in the future.